Inclusion Class Management Model in PAI Learning Based on Integration Interconnection - Kharis Syuhud Mujahada; Hanifah Noviyandri (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
This research departs from the background of the problem about researchers' anxiety about how to manage inclusion classes in PAI learning. This study uses a qualitative approach type of case study with multi site design. The technique of collecting data through observation, in-depth interviews and documentation. The results showed that: 1) Characteristics of inclusion class students in both SDN, namely: a) Normal students and b) ABK students, consisting of several types, namely autism, mental retardation, ADHD, quadriplegic, dyslexic, emotional disorders and slow leaner. 2) The GPAI strategy in managing regular classes is by classical direct learning methods and the assignment of tasks is differentiated according to students' abilities. 3) Implications of the inclusive classroom management model have a positive impact on learning outcomes, in addition students are also accustomed to applying values Islam in real life, is able to adapt, communicate and socialize well with others.